2012
DOI: 10.1371/journal.pone.0050296
|View full text |Cite
|
Sign up to set email alerts
|

Immunogenicity of Bivalent Human Papillomavirus DNA Vaccine Using Human Endogenous Retrovirus Envelope-Coated Baculoviral Vectors in Mice and Pigs

Abstract: Human papillomavirus is known to be the major pathogen of cervical cancer. Here, we report the efficacy of a bivalent human papillomavirus type 16 and 18 DNA vaccine system following repeated dosing in mice and pigs using a recombinant baculovirus bearing human endogenous retrovirus envelope protein (AcHERV) as a vector. The intramuscular administration of AcHERV-based HPV16L1 and HPV18L1 DNA vaccines induced antigen-specific serum IgG, vaginal IgA, and neutralizing antibodies to levels comparable to those ach… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
20
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 18 publications
(21 citation statements)
references
References 34 publications
0
20
0
1
Order By: Relevance
“…Such BacMam vectors carried genes that coded for L1 capsid proteins from different high-risk HPV types (bivalent and trivalent vectors). 123,[183][184][185] In these reports, animals received 3 doses of rAcMNPV via the i.m. route, rather than the i.n.…”
Section: Human Papillomavirusmentioning
confidence: 99%
See 2 more Smart Citations
“…Such BacMam vectors carried genes that coded for L1 capsid proteins from different high-risk HPV types (bivalent and trivalent vectors). 123,[183][184][185] In these reports, animals received 3 doses of rAcMNPV via the i.m. route, rather than the i.n.…”
Section: Human Papillomavirusmentioning
confidence: 99%
“…route used for the influenza virus. [183][184][185] In other work, mice were immunized through the sublingual (s.l.) route, which had the same efficacy as the i.m.…”
Section: Human Papillomavirusmentioning
confidence: 99%
See 1 more Smart Citation
“…Previously, we demonstrated that human endogenous retrovirus (HERV) enveloped, replication-deficient baculovirus delivering HPV L1 genes (AcHERV-HPV) induced high levels of humoral and cellular immunity, conferring complete protection against HPV type-specific pseudovirions (Lee et al, 2010(Lee et al, , 2012Cho et al, 2014). Here, we examined whether the trivalent HPV L1 DNA vaccine exhibits antitumor efficacy in a murine model of HPV L1-associated cervical cancer.…”
Section: Introductionmentioning
confidence: 99%
“…Este tipo de estrategia resultó más eficiente comparada a la inmunización con sus contrapartes de vacunas a DNA debido tanto a la mayor eficiencia de transducción de estos baculovirus pseudotipados como a las mencionadas propiedades adyuvantes de los mismos. Además de la proteína G de VSV, es posible utilizar otras proteínas de superficie como las derivadas de retrovirus endógenos humanos (HERV), con las que se desarrollaron vacunas experimentales bivalentes contra los HPV 16 y 18 [90] o trivalentes 16/18/58 [91].…”
Section: Tabla Ii: Vacunas Aprobadas Producidas En El Sistema Bv Paraunclassified